2018
DOI: 10.1002/jgh3.12077
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylene glycol plus bisacodyl: A safe, cheap, and effective regimen for colonoscopy in the South Asian patients

Abstract: Background and AimData regarding the comparison of colonoscopic preparation regimens are still variable. We aimed to assess the adequacy and tolerability of two bowel preparation regimens for afternoon colonoscopy.MethodsIn a randomized, investigator‐blinded trial, two preparation regimens [4‐L split‐dose polyethylene glycol‐electrolytes (PEG‐ELS) and 2‐L PEG‐ELS plus bisacodyl) were compared in terms of bowel cleansing efficacy and adverse effects.ResultsThe mean (±SD) age (years) of the 4‐L split‐dose PEG‐EL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Usual indications for colonoscopy in South Asia are gastrointestinal bleeding, abdominal pain and altered bowel habit caused by infective colitis, inflammatory bowel disease, ileocecal tuberculosis, hemorrhoids, and malignancies. [10] South Asian populations have lower body mass index, different diet habits, and shorter colonic transit time compared to Western countries. Studies from India had shown that adequate preparation for late-morning/afternoon colonoscopy can be achieved with the use of low-volume PEG-ELS with or without stimulant laxatives.…”
Section: Polyethylenementioning
confidence: 99%
See 3 more Smart Citations
“…Usual indications for colonoscopy in South Asia are gastrointestinal bleeding, abdominal pain and altered bowel habit caused by infective colitis, inflammatory bowel disease, ileocecal tuberculosis, hemorrhoids, and malignancies. [10] South Asian populations have lower body mass index, different diet habits, and shorter colonic transit time compared to Western countries. Studies from India had shown that adequate preparation for late-morning/afternoon colonoscopy can be achieved with the use of low-volume PEG-ELS with or without stimulant laxatives.…”
Section: Polyethylenementioning
confidence: 99%
“…Studies showed similar efficacy of a regimen of stimulant laxative at bedtime with 2L PEG-ELS in the morning and a 4L PEG-ELS split-dose regimen. [9,10] In a meta-analysis of six randomized controlled trials, low-volume PEG (2L) with bisacodyl demonstrates similar rates of adequate bowel cleansing and less nausea, vomiting, and bloating compared to 4L split-dose PEG-ELS. [9] In addition, the use of 2L PEG-ELS plus bisacodyl can save approximately $6 per procedure.…”
Section: Polyethylenementioning
confidence: 99%
See 2 more Smart Citations
“…The adequacy of bowel cleansing mainly depends on the type of cleansing agents, volume of preparation, mode of administration (single dose vs. split dose, single day vs. two days), use of adjunct agents, the preparation-to-colonoscopy interval, and associated comorbidities in patients. 1,2 Other factors for adequate bowel cleansing may include low residue diet, liberal fluid intake, and proper bowel preparation instructions.…”
mentioning
confidence: 99%